Length-Weight Relationship and Gonad Maturity of Marble sleeper Oxyeleotris marmorata (Bleeker, 1852) in Tondano Lake North Sulawesi - Ikky Ahdian Umage; Nego E. Bataragoa; Jety K. Rangan; Anneke V. Lohoo; Janny D. Kusen; Ruddy D. Moningkey (Sam Ratulangi University, 2022)
The purpose of this study was to determine the length-weight relationship and gonad maturity of Betutu fish (Oxyeleotris marmorata) in Lake Tondano. Fish samples were caught using gill nets and lift nets in Lake Tondano. Total catches of 240 individuals. The legth-weight relation of male fish is W = 0.0094 L3.14 positive allometric growth pattern. Female female fish obtained W = 0.0104 L3.11 positive allometric growth patterns. The condition factor for male fish is 1.46 male and 1.47 female respectively. All levels of gonad maturity (I, II, III, IV and V) were found in each sample both in August and September. The size of the first mature male male fish is 219 ± 3 mm (range in size 216-222 mm) and female fish 171 ± 3 (range in size 169-174 mm).Keywords: Length-Weight, gonad maturity, Tondano Lake ABSTRAKTujuan penelitian ini untuk mengetahui hubungan panjang-berat dan kematangan gonad ikan Betutu (Oxyeleotris marmorata) yang ada di danau Tondano. Sampel ikan ditangkap menggunakan jaring insang dan jaring angkat di danau Tondano. Total hasil tangkapan 240 individu. Hubungan panjang-berat ikan betutu jantan yaitu W = 0,0094L3,1394 pola pertumbuhan allometrik positif. Ikan betutu betina didapatkan W = 0,0104L3,1137 pola pertumbuhan allometrik positif. Faktor kondisi ikan betutu jantan masing-masing sebesar 1,46 ikan jantan dan 1,47 ikan betina. Seluruh tingkat kematangan gonad (I, II, III, IV dan V) ditemukan pada setiap sampel baik pada bulan agustus maupun bulan September. Ukuran pertama kali matang ikan betutu jantan yaitu 219 ±3 mm (kisaran ukuran 216-222 mm) dan ikan betina 171±3 (kisaran ukuran 169-174 mm)Kata Kunci: Panjang-berat, kematangan gonad, Danau Tondano